(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This article aims to explore the role of Toraja customs in encouraging women’s participation in the 2024 legislative elections in Toraja, Indonesia, with a focus on the political legitimacy provided by customs and the church and the role of women as agents of political change. A qualitative approach was used in this study with a case study design. Data were collected through in-depth interviews with eight key informants, including traditional leaders, religious leaders, and female politicians. Data analysis was conducted using grounded theory techniques, applying thematic analysis to identify patterns and categories in the data. This study found that Toraja customs serve as a source of political legitimacy for women, with customary approval strengthening women’s involvement in politics. The principle of tallu bakaa (wise, intelligent, brave, economically stable) is the main guideline in selecting leaders, and this applies equally in the customary and formal political spheres. The Toraja church also provides significant support for women’s involvement in politics, despite initially limiting their roles. Toraja women, with the support of customs and the church, have strong social capital to engage in formal politics. This study concludes that Toraja customs and the Toraja church play an important role in encouraging women’s participation in Toraja politics, which is based on the principles of gender equality and customary deliberation. Customs and the church provide social and cultural legitimacy, while education and cultural values such as tallu bakaa give women the confidence to engage in formal political contests.